Epidemiology and pre-vaccine burden of rotavirus diarrhea in Democratic Republic of Congo (DRC): Results of sentinel surveillance, 2009–2019. Issue 41 (29th September 2022) - Luhata Lungayo, Christophe; Burke, Rachel M.; Cikomola, Aimé; Mukamba, Elisabeth; Burnett, Eleanor; Tate, Jacqueline E.; Samuel Otomba, John; Albert, Mbule K.; Nimpa, Marcellin M.; Dommergues, M.A.; Pukuta, Elisabeth; Mwenda, Jason M.; et al.
Abstract: Introduction: Since August 2009, the Democratic Republic of Congo (DRC) has implemented sentinel site surveillance for rotavirus gastroenteritis. Limited hospital studies have been carried out, in DRC, describing the epidemiology of rotavirus diarrhea before rotavirus vaccine introduction in October 2019. This analysis describes the epidemiology of rotavirus gastroenteritis and characteristics of circulating viral strains from 2009 to 2019. Materials and methods: We analyzed demographic and clinic data collected from children < 5 years old enrolled at three rotavirus sentinel surveillance sites in DRC during 2009–2019, prior to rotavirus vaccine introduction in 2019. Data have been described and presented as mean ± standard deviation for quantitative variables with normal distribution, or as median with an interquartile range [Q1-Q3] for quantitative variables with non-normal distribution, or as absolute value with percentage for qualitative variables. Results: Between August 2009 and December 2019, 4, 928 children < 5 years old were admitted to sentinel surveillance sites for gastroenteritis in the DRC; the rotavirus positivity rate was 60 %. There was a slight male gender predominance (56 %), and the majority of children (79 %) were 0–11 months of age. Every year, the incidence was highest between May and September corresponding to the dry and cool season. Genotyping was performed for 50 % of confirmed rotavirus cases. The most common G genotypes were G1 (39 %) and G2 (24 %) and most common P genotypes were P[6] (49 %) and P[8] (37 %). The most common G-P genotype combinations were G1P[8] (22 %), G2P[6] (16 %) and G1P[6] (14 %). Genotype distribution varied by site, age group, and year. Conclusion: From 2009 to 2019, rotavirus-associated gastroenteritis represented a significant burden among DRC children under 5 who were admitted to sentinel sites. G1P[8] was the most commonly identified genotype. Continued monitoring after the introduction of rotavirus vaccine will be essential to monitor any changes in epidemiology.